Frequency‐Driven Self‐Organized Helical Superstructures Loaded with Mesogen‐Grafted Silica Nanoparticles. Issue 42 (6th October 2016) - Gutierrez‐Cuevas, Karla G.; Wang, Ling; Zheng, Zhi‐gang; Bisoyi, Hari K.; Li, Guoqiang; Tan, Loon‐Seng; Vaia, Richard A.; Li, Quan
Abstract: Adding colloidal nanoparticles into liquid‐crystal media has become a promising pathway either to enhance or to introduce novel properties for improved device performance. Here we designed and synthesized new colloidal hybrid silica nanoparticles passivated with a mesogenic monolayer on the surface to facilitate their organo‐solubility and compatibility in a liquid‐crystal host. The resulting nanoparticles were identified by 1 H NMR spectroscopy, TEM, TGA, and UV/Vis techniques, and the hybrid nanoparticles were doped into a dual‐frequency cholesteric liquid‐crystal host to appraise both their compatibility with the host and the effect of the doping concentration on their electro‐optical properties. Interestingly, the silica‐nanoparticle‐doped liquid‐crystalline nanocomposites were found to be able to dynamically self‐organize into a helical configuration and exhibit multi‐stability, that is, homeotropic (transparent), focal conic (opaque), and planar states (partially transparent), depending on the frequency applied at sustained low voltage. Significantly, a higher contrast ratio between the transparent state and scattering state was accomplished in the nanoparticle‐embedded liquid‐crystal systems. Abstract : Frequency‐driven self‐organized helical superstructures were fabricated by incorporating mesogen‐grafted silica nanoparticles into a dual‐frequency cholesteric liquid‐crystal host. The resultant nanocomposites were able to display multiple stable states, that is, transparent, opaque, and partially transparent, depending on the frequency applied at sustained low voltage.